2014
DOI: 10.1016/j.jalz.2014.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Stress, PTSD, and dementia

Abstract: The physiological consequences of acute and chronic stress on a range of organ systems have been well documented after the pioneering work of Hans Selye more than 70 years ago. More recently, an association between exposure to stressful life events and the development of later-life cognitive dysfunction has been proposed. Several plausible neurohormonal pathways and genetic mechanisms exist to support such an association. However, many logistical and methodological barriers must be overcome before a defined ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(109 citation statements)
references
References 76 publications
7
102
0
Order By: Relevance
“…We have also found that high neuroticism, a stress-prone personality trait, and increased number of stressful life events were related to AD risk [3,4]. Other longitudinal studies have reported associations between stress disorders (e.g., posttraumatic stress disorder), stress-prone personality, and dementia [5,6].…”
Section: Introductionsupporting
confidence: 69%
“…We have also found that high neuroticism, a stress-prone personality trait, and increased number of stressful life events were related to AD risk [3,4]. Other longitudinal studies have reported associations between stress disorders (e.g., posttraumatic stress disorder), stress-prone personality, and dementia [5,6].…”
Section: Introductionsupporting
confidence: 69%
“…It will also be valuable to examine the potential role of alterations in the CAB relative to cognitive impairment in PTSD, perhaps especially so in older adults, as PTSD is associated with cognitive dysfunction and is a known risk factor for dementia [49,50]. Future studies using high-density fiber tracking, "brain bank" data, and multi-modal imaging techniques may better elucidate the relationship between both gray and white matter integrity alterations in PTSD.…”
Section: Resultsmentioning
confidence: 99%
“…70 Chronic mental stress is a risk factor for AD. [77][78][79][80] Since mental stress has a negative impact on cerebral vascular function, [81][82][83] and, specifically, increases the risk of cerebral atherosclerosis 84 and vasospasm 85 it may be considered a VRF. Interestingly, meditation provides stress relief and improves cerebral blood flow 86,87 and does so in subjects with memory loss.…”
Section: Interventions To Treat Vrfsmentioning
confidence: 99%